Interface-dependent nucleation in nanostructured layered composites - Irene J. Beyerlein; Jian Wang; Ruifeng Zhang (APL Materials, 2013)
Nanocomposite properties are to a large extent governed by interface-associated mechanisms. Via atomic-scale modeling of bi-phase interfaces, we reveal a strong correlation between interface structure and the nucleation of dislocations. We show that the number and types of dislocations that are emitted depend sensitively on a few key structural features of the interface. Based on these insights, a model is developed that connects nucleation propensity with interface structure. This finding implies that tuning interface structure is a conceivable approach for strengthening nanocomposites, one that is distinct from the common strategy of shrinking nanostructure dimensions.